The role of N-terminal pro-brain natriuretic peptide as an early alert of pulmonary hypertension in chronic lung disease - Hulaimi; Yanti, Budi; Ridwan, Muhammad; Arliny, Yunita; Nurrahmah (Universitas Brawijaya, 2026)
BACKGROUND: One of the primary causes of illness and dying in worldwide was chronic lung disease (CLD). Pulmonary hypertension (PH) was among the most popular issues linked to CLD, often remaining undiagnosed in the early stages. N-terminal pro-brain natriuretic peptide (NT-proBNP) and electrocardiographic abnormalities could be early alert of pulmonary hypertension. OBJECTIVES: This study aims to ascertain the role of NT-proBNP as early markers of pulmonary hypertension in CLD. METHOD: This study used a cross-sectional design in 2024, and there where 35 patients with CLD were analyzed. A group of normal individuals without cardiac and pulmonary abnormalities was used as a control group. Data on patient characteristics, symptoms, typical electrocardiography (ECG) results of pulmonary hypertension, as well as serum NT-proBNP levels was measured at baseline before any intervention. RESULTS: Most patients were male (85.7%) and aged ≥60 years (51.4%), and Chronic Obstructive Pulmonary Disease (COPD) is the most popular CLD (65.7%). Prolonged QT (20%) was the most prevalent ECG abnormality, followed by right axis deviation (14.7%) and Right Bundle Branch Block (11.42%). The COPD group had the most elevated NT-proBNP levels (mean 90.22 pg/mL), then the Pulmonary Tuberculosis Lung Disease group at 74.34 pg/mL, and in normal individuals (57.89 pg/mL). The NTproBNP levels differed significantly amongst the groups (p = 0.0215). CONCLUSION: COPD, which is the most CLD, showed the highest prevalence of early pulmonary hypertension, characterized by increased NT-proBNP and QT prolongation. In CLD, NT-proBNP could be utilized as an indicator of the initial identification of pulmonary hypertension.